TOWARDS ZERO EMISSIONS: A CRITICAL REVIEW OF THE CONTRIBUTION OF THE GREEN ECONOMY TO GLOBAL CLIMATE CHANGE TARGETS - Loso Judijanto; Mohd Syahrin (CV. ADIBA AISHA AMIRA, 2025)
Global climate change has become a major challenge that requires appropriate mitigation and adaptation measures, one of which is through the implementation of a green economy. A green economy focuses on integrating economic growth, environmental sustainability, and social justice to achieve global targets toward net- zero carbon emissions. This article critically examines the contribution of a green economy to carbon emission reduction and the challenges it faces, particularly in developing countries. Constraints such as unequal access to technology, lack of funding, and the dominance of fossil-based energy systems are significant barriers to the implementation of a green economy. To achieve zero emissions, global commitment through green investment, technology transfer, and inclusive international cooperation is required. The conclusion of this study emphasises the importance of cross-sectoral and cross-national synergies in efforts to achieve a more sustainable economy in order to effectively address the climate crisis.